Characteristics and origin of desorption gas of the Permian Shanxi Formation shale in the Ordos Basin, China. Issue 6 (November 2017) - Sun, Zepeng; Wang, Yongli; Wei, Zhifu; Zhang, Mingfeng; Wang, Gen; Wang, Zixiang
The Lower Permian Shanxi Formation marine–continental transitional organic-rich shale is one of the most important potential shale gas plays in the Ordos Basin, China. However, the content and origin of desorbed gas from the Shanxi Formation are poorly documented, limiting the understanding of gas generation and potential play elements. Geochemical characteristics of desorbed gas, including content and origin, are analyzed from 17 core samples of the Shanxi Formation from well SL-1. The results show that the Shanxi Formation shales in the study area are characterized by high total organic carbon content of 1.17–2.63%, type III organic matter, and high Tmax between 493 and 513℃. The desorbed gas content of the shale samples varies from 0.22 to 0.50 m 3 /t, with an average of 0.37 m 3 /t, and shows a positive correlation with total organic carbon. The gases are dominated by methane (69.57–89.02%), with small amounts of ethane (0.01–0.09%). The carbon isotopic signature δ 13 C1 ranges from −49.5 to −45.3‰, and the δ 13 C2 ranges from −23.3 to −14.7‰. In addition, gases released from the Shanxi Formation core samples are thermogenic in origin and possibly coal derived, as the Whiticar chart and the diagram of ethane versus δ 13 C2 suggest.